PEMBELAJARAN GEOGRAFI DENGAN SISTEM PEMBELAJARAN ONLINE DIMASA PANDEMI DI KELAS X SMAN 1 MENYUKE - Irena Riski Apriliandra; Aminuyati Aminuyati; L.M. Hari Christanto (Universitas Tanjungpura, 2021)
AbstractThe purpose of the study was to analyze geography learning with an online learning system during the covid-19 pandemic in class X IIS Menyuke High School, Landak Regency. This study aims to determine the planning, implementation and assessment of geography learning with an online learning system during the covid-19 pandemic in class X IIS SMA Menyuke High School, Landak Regency. This research uses naturalistic inquiry qualitative research method which produces descriptive data. Sources of research are the principal, geography teacher and students of class X IIS Menyuke High School. The procedures for collecting research data are observation, interviews and documentation studies. The data collection tools used were observation sheets, interview guidelines, and documents such as archives such as student data, student score data. Data analysis in research is data collection, data reduction, data presentation, verification and drawing conclusions. Based on the results of the study, learning geography with an online system at Menyuke High School Landak Regency includes 3 processes, namely planning, implementation and assessment. Planning is in the form of collecting data on student conditions and phone numbers and then creating WhatsApp groups, making lesson plans, preparing materials, and determining media. Implementation is in the form of introduction, core activities and closing of learning. Skills assessment is seen from the results of project assignments, products and portfolios. Learning geography with an online system can still be carried out during the COVID-19 pandemic.Keywords: Covid-19 Pandemi, Geography Learning, Online Learning